Learning and attention disorders in adolescence and adulthood : assessment and treatment - Goldstein, Sam, 1952-; Naglieri, Jack A.; DeVries, Melissa (Hoboken, N.J. : John Wiley & Sons, 2011)
"With informed support, students at the K-12 and collegiate levels can overcome the obstacles of ADHD and other learning disabilities. Drawing on evidence-based techniques, this book provides school psychologists, counselors, and consultants with the best diagnoses and treatments to help their clients become effective students. It includes a thorough overview of LD and ADHD, as well as a set of guidelines to assist adolescents and adults. This is important reading for practitioners in education and mental health working to create learning programs"--Provided by publisher.
Learning and Attention Disorders in Adolescence and Adulthood: Assessment and Treatment; Contents; Acknowledgments; Contributors; Preface; Part I: Background; 1: The Changing Face of LD and ADHD in Late Adolescence and Adulthood: Sam Goldstein and Melissa DeVries; 2: Learning Disabilities in Childhood: Sam Goldstein; 3: Attention-Deficit/Hyperactivity Disorder in Childhood: Sam Goldstein and Melissa DeVries; 4: Adults with Learning Disabilities: Barriers and Progress: Noel Gregg; 5: Children with ADHD Grown Up: Kevin M. Antshel and Russell Barkley; Part II: Assessment.
Includes bibliographical references and indexes.
Print version record.
Keywords: Attention-deficit disorder in adults; Attention-deficit disorder in adolescence; Learning disabilities; Attention-deficit disorder in adolescence; Attention-deficit disorder in adults; Learning disabilities; PSYCHOLOGY -- Mental Illness; Attention-deficit disorder in adolescence; Attention-deficit disorder in adults; Learning disabilities; Learning Disorders -- therapy; Adolescent; Adult; Attention Deficit Disorder with Hyperactivity -- diagnosis; Attention Deficit Disorder with Hyperactivity -- therapy; Child; Learning Disorders -- diagnosis; Psychotherapy -- methods; Electronic books